Thermophysical Properties of Industrial Sugar Cane Juices for the Production of Bioethanol - Astolfi-Filho, Zailer [UNESP]; Minim, Luis A.; Telis-Romero, Javier [UNESP]; Minim, Valeria P. R.; Telis, Vania R. N. [UNESP] (Amer Chemical Soc, 2010)
To design equipment for biofuel production and all optimizing process for heating, settling, and filtration of industrial sugar cane juices, the thermophysical properties Must be known. Since the thermophysical properties of biological materials are strongly dependent upon chemical composition and temperature, composition- and temperature-based models provide a means of estimating these properties. In this work, the thermophysical properties of untreated sugar cane juice (USCJ), mixed Sugar cane juice (MSCJ), and clarified sugar cane juice (CSCJ) were determined at a temperature range of (277.4 to 373.4) K. Simple polynomial models as a function of temperature were fitted to the experimental data, showing good agreement. Thermal conductivity and heat capacity varied front (0.475 to 0.493) W.m(-1).K(-1) and (3601.8 to 3802.9) J.kg(-1).K(-1), respectively. Density varied from (1044.5 to 1189.5) kg.m(-3).